(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2025)
This article is devoted to the study and analysis of the legal mechanisms for combating corruption in the Republic of Uzbekistan and the ways to improve them in accordance with international standards and national development priorities. Corruption remains one of the most complex socio-legal problems that negatively affects the efficiency of public administration, economic stability, and the trust of citizens in state institutions. In recent years, Uzbekistan has made significant progress in forming a comprehensive anti-corruption policy framework, introducing institutional reforms, and aligning national legislation with global best practices. The article examines the essence of corruption as a legal and moral phenomenon, its causes and consequences, as well as the role of legal mechanisms in its prevention and suppression. Special attention is given to the Law of the Republic of Uzbekistan “On Combating Corruption,” the functions of the Anti-Corruption Agency, and the implementation of the “National Anti-Corruption Strategy for 2021–2025.” The research emphasizes that effective anti-corruption measures require not only the existence of laws but also their consistent enforcement, transparency in public administration, and civic participation in monitoring government activities. Furthermore, the paper analyzes international experiences—particularly the practices of countries such as Singapore, South Korea, and Georgia—in creating institutional frameworks for corruption prevention, enhancing public service ethics, and ensuring accountability. The study suggests that integrating these best practices into Uzbekistan’s legal system could contribute to strengthening the rule of law and promoting integrity in both public and private sectors. In conclusion, the article argues that combating corruption should be approached comprehensively—combining legal, institutional, and educational tools to create an environment of zero tolerance toward corrupt behavior. Continuous improvement of legal mechanisms, digitalization of public services, effective financial monitoring, and raising citizens’ legal awareness are identified as key directions for the future. The research findings can serve as a theoretical and practical basis for developing further reforms in the field of anti-corruption law and policy in Uzbekistan.